Динамика численности представителей семейства Cervidae на территории НПП «Гомольшанские леса» - Скоробогатов, Е.В.; Солодовникова, О.В.; Деркач, М.А. (Харьковский национальный университет имени В.Н.Каразина, 2010)
Приведены результаты мониторинга Capreolus capreolus Linnaeus, 1758, Cervus elaphus Linnaeus, 1758 и Alces alces Linnaeus, 1758 в угодьях НПП «Гомольшанские леса» и на соседних территориях. Проанализированы особенности зимнего распределения указанных видов в угодьях. Установлено: 44,2– 67,1 % местного поголовья косули в зимний период держатся в центральных лесных кварталах; 19,6– 35,9 % – в 750-метровой зоне от опушечной линии; 13,4–24,0 % – в перелесках и лесопосадках. Плотность оленьих (в «косульем эквиваленте») – 16,7–25,5 особ./1000 га. Оценена кормовая ёмкость угодий НПП. Установлено их использование менее чем на 50%, что позволяет более чем вдвое увеличить местное поголовье копытных.
Dynamics of numbers of representatives of Cervidae on the territory of the National Natural Park “Gomol’shansky lisy”
Results of monitoring of Capreolus capreolus Linnaeus, 1758, Cervus elaphus Linnaeus, 1758 and Alces alces Linnaeus, 1758 in the National Natural Park “Gomol’shansky lisy” and neighboring territories have been presented. Specificities of winter distribution of these three species in the forests relative to forest edge have been analyzed. Using winter feeding resource by ungulates has been estimated. It has been revealed that 44.2–67.1 % of local population of roe deer is in central forest square in winter period; 19.6–35.9 % – in 750 m zone of forest edge; 13,4–24,0 % – in field woodlands and tree-plantings. Density of ungulates (in “roe deer’s equivalent”) is 16,7–25,5 animals/1000 hectares. Feeding capacity of the National Natural Park forests is used less than 50%, it allows to increase the local ungulates population more than by twice.
Keywords: косуля; олень; лось; учёт по дефекациям; распределение; величина популяции; roe deer; red deer; elk; register by defecation; distribution; population size